Foraging in the Tennessee River Valley, 12,500 to 8,000 years ago - Hollenbach, Kandace D. (Book collections on Project MUSE., 2009)
Plants are inarguably a significant component of the diets of foraging peoples in non-arctic environments. As such, the decisions and activities associated with the gathering and exploitation of plants are important to foragers' subsistence pursuits. Plant remains are particularly important for understanding gathering activities. Inasmuch as plant foods comprised a considerable portion of early foragers' diets, and the gathering and processing of these plant resources occupied a significant proportion of the population, namely women, children, and the elderly, an understanding of gathering act.